(untitled) (ACTA MEDICA PERUANA, 2022)
Objective: Identify whether the reason for care influences the waiting time in the health facility in the PeruvianpopulationduringtheCOVID-19 pandemic,according to analysis by ENAHO2020. Material and Methods: Crosssectional study with secondary analysis of data from the ENAHO of the Institute of Statistics and Informatics (INEI) done in year 2020. For the analysis, regarding the reason for going to the health facility, symptoms were considered compatible with COVID- 19 and other acute symptoms. Results: Data of 1363 participants were analyzed No association was found between reason for consultation and waiting time. In the multivariate analysis found an association with female sex (PR: 2,97; IC: 1,09 – 1,54), being attended in centers of Ministerio de Salud (MINSA) establishment (PR:2,18; CI: 1,02 – 1,59)) and be attended by a doctor (PR: 6,52; IC: 1,53 – 2,21). Conclusión: Variables that have association with longer waiting time were female sex, MINSA as establishment of attendance and profesional of attendane is the doctor.